Characterizing Life-Cycle Wealth Distributions in Canada Using Dominance Criteria - Fazley K. Siddiq; Charles M. Beach (Queen's University, Department of Economics, 1993)
This paper examines how the distribution of household wealth in Canada varies with age over the life cycle. The wealth distribution is characterized in terms of decile means and decile shares for each of six age groups, and comparisons between age-specific distributions are based on first- and second-order stochastic dominance criteria. It is found that (i) mean wealth levels and wealth distributions increase significantly with age in concave quadratic fashion until near retirement and then decline, and (ii) wealth inequality declines in convex function with age, at first steeply and then not significantly. This joint pattern in mean and inequality of wealth holdings across age groups presents a challenge for basic theories to explain.
Keywords: 330